Crossing Disciplinary Boundaries to Improve Technology-Rich Learning Environments. Issue 3 (March 2017) - Lajoie, Susanne; Poitras, Eric
Background: The capacity of instructional technologies to personalize instruction has progressively improved over the last decade, in conjunction with changes in learning theories that dictate what, when, and how to support learners. Focus of Study: This paper reviews several technology-rich learning environments that are investigated by members of the Learning Environments Across Disciplines partnership, including Newton's Playground, the War of 1812 iHistory tours, Crystal Island, BioWorld, and MetaTutor. The adaptive capabilities of these systems are discussed in terms of the metaphors of using computers as cognitive, metacognitive, and affective tools. Research Design: Researchers rely on convergent methodologies to collect data via multiple modalities to gain a better understanding of what learners know, feel, and understand. The design guidelines of these learning environments are used to situate this understanding as a means to generalize best practices in personalizing instruction. Conclusions: The findings of these investigations have significant implications for the metaphor of using technology as a tool to augment our thinking. The challenge is now to broaden learning theories while taking into consideration the social and emotional perspective of learning, as well as to leverage recent advances in learning analytics and data-mining techniques to iteratively improve the design of technology-rich learning environments.